Tom Is Not More Likely to Imitate Lisa Than Ying: The Influence of a Model’s Race Indicated by Physical Appearance on Children’s Imitation - Krieger, Andrea A. R.; Möller, Corina; Zmyj, Norbert; Aschersleben, Gisa (Frontiers in Psychology, 2016)
Recent research has shown that infants and young children up to the age of five years are more likely to imitate in-group members than out-group members. Cues like gender, race, age, and language are robust indicators for social categories and, thus, for group membership. Concerning imitation, research mainly focuses on language and accent, whereas race indicated by physical appearance is rarely investigated. Research has shown that the aforementioned factors served as indicators of group membership and influenced children’s imitative behavior in such ways that the in-group member was more likely to be imitated. Nevertheless, the question arises how physical appearance of a person itself influences the imitative behavior. In this study, we investigated the effect of group membership (in-group vs. out-group) in four-year-old children (N = 48) on children’s imitative behavior. Children observed either an in-group or an out-group model (German vs. Chinese), defined by physical appearance only, which presented novel manual actions in four different tasks. After each presentation, children got the opportunity to imitate the target actions. Furthermore, children were either assigned to a live or a video condition to control for the influence of the presentation mode. Results indicated that four-year-old children did not imitate the in-group model more often than the out-group model. Furthermore, there was not difference between the two presentation modes. Results were discussed on the basis of research on the in-group-out-group effect. We suggested that a pure difference in the model’s physical appearance might not be sufficient to elicit an in-group-out-group effect.